The impact of the credit rating of the ESG debt instruments’ issuer on the coupon rate - Frydrych, Sylwia (Publishing House of Wroclaw University of Economics and Business, 2024)
This article investigates the potential impact of having credit ratings assigned by multiple rating agencies, including S&P, Moody’s, and Fitch, on the issuance of environmental, social and governance (ESG) bonds. It examines the impact on both the coupon rate offered and the volume of debt instruments issued. The research employed a mixed research methods approach, utilising observation methods and analysis of source data. Data for this research was obtained from the Refinitiv Eikon information database. The credit ratings of issuers as at the date of issuance of ESG instruments were analysed, focusing on the credit ratings assigned to issuers of ESG debt instruments issued between 2012 and 2021. Only instruments that were in circulation as of 31 December 2021 were included in the study. The findings suggest a potential link between the number of credit ratings an issuer possesses and both the offered coupon rate and the volume of ESG instruments issued. A review of the existing literature, both theoretical and empirical, does not provide clear evidence of how an issuer’s credit rating affects the success of debt issuance in relation to meeting ESG criteria.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 176-185
Keywords: sustainable finance; credit rating; ESG investing